Acute effects of inhaled salbutamol on the metabolic rate of normal subjects. - Amoroso, P. (1993)
BACKGROUND--This study was designed to investigate the contribution of inhaled salbutamol to the increase in resting metabolic rate found in patients with chronic airflow limitation who were receiving bronchodilator therapy. METHODS--The resting metabolic rate of 10 normal subjects (age 20-47 years, weight 42-105 kg, seven men) was studied after inhalations of salbutamol or placebo. An open canopy method of indirect calorimetry was used to measure resting oxygen consumption (VO2) and resting carbon dioxide production (VCO2). Subjects inhaled two, four, eight, or 12 puffs (100 micrograms/puff) of salbutamol or placebo in a double blind manner. Recordings of VO2 and VCO2 were made after inhalation of the four doses of salbutamol or placebo, integrated over one hour, and compared. RESULTS--VO2 and VCO2 increased in a dose dependent manner after inhaled salbutamol with a maximum effect at five minutes after inhalation. After four puffs, VO2 was 203 and 188 ml/kg/h for salbutamol and placebo respectively. After eight puffs, VO2 was 207 and 185 and VCO2 was 167 and 155 ml/kg/h. After 12 puffs, VO2 was 220 and 190 with a VCO2 of 181 and 168 ml/kg/h. Twelve puffs of salbutamol increased the mean (SE) respiratory quotient from 0.85 (0.01) to 0.93 (0.04) at five minutes indicating an increase in ventilation in excess of metabolic demand. Mean heart rate increased in parallel with VO2. CONCLUSION--Inhaled salbutamol significantly increases resting metabolic rate in a dose dependent manner.